Comparison of the mineral composition of leaves and infusions of traditional and herbal teas - Jana Olivier (South African Journal of Science, 2012)
Most research on teas has focused on organic composition and less attention has been given to the mineral composition. The aim of this study was to examine and compare the mineral compositions (Na, Mg, K, Ca, P, S, Fe, Mn, Zn, Cu and Al) of eight commonly consumed teas. The teas included three traditional black or green teas (from Africa, China and Sri Lanka) and five herbal teas – two from South America (maté and coca) and three from South Africa (rooibos, honeybush and Athrixia phylicoides). Analyses were conducted on five samples of dry tea leaves of each of the teas and their infusions (steeping time: 6 min) using identical techniques in inductively coupled plasma optical emission spectrometry (ICP-OES). It was found that each tea has a unique mineral profile. Dry tea leaves and their respective infusions also exhibited different mineral profiles. The tea infusions that contained relatively higher concentrations of beneficial minerals were maté, coca and Athrixia. High levels of aluminium were found in the traditional black and green teas whilst rooibos was high in sodium. Although teas are not rich sources of nutrients, the consumption of maté could contribute significantly to dietary manganese requirements.